Quasiclassical computation - Remacle, F. (National Academy of Sciences, 2004)
The chemical kinetic description of time evolution where the phase is random but the states are discrete is discussed as a basis for a computational approach. This proposed scheme uses numbers in the entire range of 0 to 1 to represent Boolean propositions. In the implementation by chemical kinetics these numbers are the mole fractions of different species. Vibrational relaxation in a mixture of HCl and DCI is the physical system that is used to illustrate the approach. Energy exchange in such a mixture corresponds to two strongly coupled two-level systems. A search problem, previously discussed in the quantum computing literature, is solved as an example. The solution requires the same number of function evaluations as in the quantal case. The action of the oracle is described in detail.